Surgeon-Powered Robotics in Thoracic Surgery; An Era of Surgical Innovation and Its Benefits for the Patient and Beyond - Trevis, Jason; Chilvers, Nicholas; Freystaetter, Kathrin; Dunning, Joel (Frontiers in Surgery, 2020)
Following its introduction in 1992, the growth of minimally invasive thoracic surgery was initially hampered by the lack of specialised instruments, impeded visualisation and stapling. However, in subsequent years these challenges were somewhat overcome and video-assisted thoracoscopic surgery (VATS) became the preferred modality of many centres.  More recently, robotic surgery has come to the fore.  Whilst it offers outstanding precision via robotic wristed instruments, robotic surgery is expensive and has safety implications as the surgeon is away from the patient’s side.  Wristed VATS instruments offer a new, exciting alternative.  By placing the robotic-like wristed instruments in the hands of the surgeon, a concept we call surgeon-powered robotics, the benefits of robotic surgery can be achieved by the patient’s side.  We describe our experience of the ArtiSential ® wristed instruments and discuss the benefits and challenges of this technology.  By combining wristed instruments with the latest surgeon-controlled 3D camera technology, surgeon-powered robotics is an affordable reality.